STATISTICAL ANALYSIS OF THE QUALITY OF A TECHNOLOGICAL PROCESS FOR THE PRODUCTION OF SHAFTS FOR ELECTRIC MOTORS BY ROUGHNESS STUDY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This paper presents a statistical analysis of the quality of a technological process by investigating the surface roughness of shafts for electric motors obtained during machining. Repeated measurements have been carried out using a portable roughness tester INSIZE ISR - C002 and the results are summarized. Statistical analysis is applied to analyse the accuracy, adjustability, and stability of technological process. The stability of the process is presented by investigating the correlation between the experimental and theoretical curve of the quality index. Accuracy evaluation is performed by calculating the accuracy coefficient. The adjustability analysis is evaluated by the relative position of the distribution curve of the obtained quality index with respect to the tolerance field.